Skeletal muscle atrophy: From mechanisms to treatments. (October 2021) - Yin, Lin; Li, Na; Jia, Weihua; Wang, Nuoqi; Liang, Meidai; Yang, Xiuying; Du, Guanhua
Abstract: Skeletal muscle is a crucial tissue for movement, gestural assistance, metabolic homeostasis, and thermogenesis. It makes up approximately 40% of the total body weight and 50% of total protein. However, several pathological abnormalities (e.g., chronic diseases, cancer, long-term infection, aging) can induce an imbalance in skeletal muscle protein synthesis and degradation, which triggers muscle wasting and even leads to atrophy. Skeletal muscle atrophy is characterized by weakening, shrinking, and decreasing muscle mass and fiber cross-sectional area at the histological level. It manifests as a reduction in force production, easy fatigue and decreased exercise capability, along with a lower quality of life. Mechanistically, there are several pathophysiological processes involved in skeletal muscle atrophy, including oxidative stress and inflammation, which then activate signal transduction, such as the ubiquitin proteasome system, autophagy lysosome system, and mTOR. Considering the great economic and social burden that muscle atrophy can inflict, effective prevention and treatment strategies are essential but still limited. Exercise is widely acknowledged as the most effective therapy for skeletal muscle atrophy; unfortunately, it is not applicable for all patients. Several active substances for skeletal muscle atrophy have been discovered and evaluated in clinical trials, however, they have not been marketed to date. Knowledge is being gained on the underlying mechanisms, highlighting more promising treatment strategies in the future. In this paper, the mechanisms and treatment strategies for skeletal muscle atrophy are briefly reviewed. Graphical Abstract: ga1